1998
DOI: 10.4269/ajtmh.1998.58.768
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and lack of immune response to Plasmodium falciparum P126 antigen and its amino-terminal repeat in malaria-infected humans.

Abstract: Abstract. A parasitophorous vacuole protein of Plasmodium falciparum, p126, is a potential candidate for a malaria vaccine. Its N-terminal region, composed of six repeats of eight amino acids, appears to be involved in the induction of protective immunity against P. falciparum challenge in monkeys. This study evaluated the immune response to p126 and to its N-terminal region (Nt47) in patients (n ϭ 45) living in a malaria-endemic area of Brazil (Colina, Porto Velho, Rondonia). Cellular proliferative responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
6
28
0
Order By: Relevance
“…Data on humoral responses to p126 and Nt47 are shown in Table 1. Antibodies against p126 protein were found in all malariaexposed donors (100% for Colina and Ribeirinha), confirming our earlier observation that this protein is a good immunogen 16,29 under natural conditions of exposure. Five percent (4 of 78) of the Porto Velho group presented antibodies against p126.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Data on humoral responses to p126 and Nt47 are shown in Table 1. Antibodies against p126 protein were found in all malariaexposed donors (100% for Colina and Ribeirinha), confirming our earlier observation that this protein is a good immunogen 16,29 under natural conditions of exposure. Five percent (4 of 78) of the Porto Velho group presented antibodies against p126.…”
Section: Resultssupporting
confidence: 72%
“…Nevertheless, in a previous study in which we examined the biologic activity of specific antibodies, we observed that anti-Nt47 cytophilic IgG of isotypes 1 and 3 could have an important role in the control of parasitemia loads in P. falciparum-infected humans. 16 The predominantly positive response to Nt47 observed in HLA-DR4 people was independent of the presence of any particular HLA allele. The small number of nonresponders carried the same alleles as their counterparts.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations